Laudatio professoribus. Celebrating the Anniversaries of the Two Most Important Scholars of Classical Philology in Lithuania - Biržietienė, Skirmantė (Respectus Philologicus, 2024)
Review of the scholarly activities on the occasion of the anniversaries of scholars of  Antiquity and Lithuanian Renaissance and Baroque, translators Dalia Dilytė-Staškevičienė and Eugenija Ulčinaitė.